Product/Service‐Systems for a Circular Economy: The Route to Decoupling Economic Growth from Resource Consumption? - Kjaer, Louise Laumann; Pigosso, Daniela C. A.; Niero, Monia; Bech, Nynne Marie; McAloone, Tim C. (Journal of industrial ecology, 2019)
Summary Product/service‐systems (PSS) that focus on selling service and performance instead of products are often mentioned as means to realize a circular economy (CE), in which economic growth is decoupled from resource consumption. However, a PSS is no implicit guarantee for a CE, and CE strategies do not necessarily lead to decoupling economic growth from resource consumption in absolute terms. Absolute resource decoupling only occurs when the resource use declines, irrespective of the growth rate of the economic driver. In this forum paper, we propose a two‐step framework that aims to support analyses of PSS and their potential to lead to absolute resource decoupling. In the first step, we present four PSS enablers of relative resource reduction that qualify as CE strategies. In the second step, three subsequent requirements need to be met, in order to successfully achieve absolute resource decoupling. Conditions and limitations for this accomplishment are discussed. Danish textile cases are used to exemplify the framework elements and its application. We expect that the framework will challenge the debate on the necessary conditions for CE strategies to ensure absolute resource decoupling.